2014
DOI: 10.1016/j.bmc.2013.12.065
|View full text |Cite
|
Sign up to set email alerts
|

3-Ketone-4,6-diene ceramide analogs exclusively induce apoptosis in chemo-resistant cancer cells

Abstract: Multidrug-resistance is a major cause of cancer chemotherapy failure in clinical treatment. Evidence shows that multidrug-resistant cancer cells are as sensitive as corresponding regular cancer cells under the exposure to anticancer ceramide analogs. In this work we designed five new ceramide analogs with different backbones, in order to test the hypothesis that extending the conjugated system in ceramide analogs would lead to an increase of their anticancer activity and selectivity towards resistant cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Several studies have reported that ceramide is intimately involved in cancer pathogenesis. Alterations in its metabolism are involved in regulation of cancer initiation, progression, and/or response to chemotherapeutic agents and radiation [ 16 , 32 , 33 ]. However, the clinical relevance of ceramide levels in patients with breast cancer remains unclear, due to lack of accurate measurement of ceramides in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that ceramide is intimately involved in cancer pathogenesis. Alterations in its metabolism are involved in regulation of cancer initiation, progression, and/or response to chemotherapeutic agents and radiation [ 16 , 32 , 33 ]. However, the clinical relevance of ceramide levels in patients with breast cancer remains unclear, due to lack of accurate measurement of ceramides in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide analog 315 has been previously shown to be anti-proliferative and cytotoxic to human breast cancer cells in vitro [12]. This compound has an imine functional group in the ceramide side-chain, and an amide functional group replacing the allyl alcohol group in the ceramide backbone [9].…”
Section: Discussionmentioning
confidence: 99%
“…1) Extension of the conjugated system in the ceramide backbone and/or side-chain increases the potency; 2) Phenyl imine group modification on the side-chain (especially ortho-substituted phenyl) enhances the anti-cancer potency; 3) 1-Position modification results in GCS (Glucosylceramide Synthase) inhibition; and 4) Ceramides can induce apoptosis and inhibit cell growth and proliferation in in vitro studies [912]. Despite recent advances in the treatment of cancer, triple negative breast cancer is very aggressive and difficult to treat [4], posing an important clinical challenge due to unresponsiveness to endocrine- and chemo-therapies.…”
mentioning
confidence: 99%
“…21,22 For the synthesis of analog 403, D-sphingosine was reacted with phenylacetyl chloride in the presence of sodium bicarbonate as a base and dichloromethane as solvent to get analog 403. 23…”
Section: New Ceramide Analogs 315 and 403 Synthesismentioning
confidence: 99%